CONVERGENT AND DIVERGENT THINKING IN PROBLEM SOLVING (CASE STUDY ON JUNIOR HIGH SCHOOL STUDENTS) - Saleh, Hairus (Universitas Negeri Malang, 2019)
This research involves 38 JUNIOR students with math skills vary, 12 students with high math ability, 18 students with the capabilities of the math medium, and 8 students with a mathematical ability is low. The entire students are asked to work on the problem-solving tests individually, with its main focus are as follows: (1) students were asked to write down what was known to be reserved; (2) write back what is asked the question; (3) write the problem resolution plan; (4) to resolve the issue in accordance with the plans that have been written; (5) try the other possible alternative in resolving problems; (6) rechecking problem resolution. The findings show that students answer math problems solving has diversity which is categorized into four categories: no changes mean, a variability of blind, orthodoxy, and creativity. Students in the creative categories are students who can solve problems by integrating CT and DT by using two models: the CDM and DCM. Students in this category can have opportunities to create and explore the variability.